Xylan catabolism is improved by blending bioprospecting and metabolic pathway engineering in Saccharomyces cerevisiae. Issue 4 (18th March 2015) - Lee, Sun‐Mi; Jellison, Taylor; Alper, Hal S.
Abstract Complete utilization of all available carbon sources in lignocellulosic biomass still remains a challenge in engineering Saccharomyces cerevisiae. Even with efficient heterologous xylose catabolic pathways, S. cerevisiae is unable to utilize xylose in lignocellulosic biomass unless xylan is depolymerized to xylose. Here we demonstrate that a blended bioprospecting approach along with pathway engineering and evolutionary engineering can be used to improve xylan catabolism in S. cerevisiae. Specifically, we perform whole genome sequencing‐based bioprospecting of a strain with remarkable pentose catabolic potential that we isolated and named Ustilago bevomyces. The heterologous expression of xylan catabolic genes enabled S. cerevisiae to grow on xylan as a single carbon source in minimal medium. A combination of bioprospecting and metabolic pathway evolution demonstrated that the xylan catabolic pathway could be further improved. Ultimately, engineering efforts were able to achieve xylan conversion into ethanol of up to 0.22 g/L on minimal medium compositions with xylan. This pathway provides a novel starting point for improving lignocellulosic conversion by yeast.